Scientific characterization methods for better utilization of cattle dung and urine: a concise review - Singh Y.; Rani J.; Kushwaha J.; Priyadarsini M.; Pandey K.P.; Sheth P.N.; Yadav S.K.; Mahesh M.S.; Dhoble A.S. (My University, 2025)
Cattle are usually raised for food, manure, leather, therapeutic, and draught purposes. Biowastes from cattle, such as dung and urine, harbor a diverse group of crucial compounds, metabolites/chemicals, and microorganisms that may benefit humans for agriculture, nutrition, therapeutics, industrial, and other utility products. Several bioactive compounds have been identified in cattle dung and urine, which possess unique properties and may vary based on agro-climatic zones and feeding practices. Therefore, cattle dung and urine have great significance, and a balanced nutritional diet may be a key to improved quality of these products/by-products. This review primarily focuses on the scientific aspects of biochemical and microbial characterization of cattle biowastes. Various methods including genomics for analyzing cattle dung and gas chromatography-mass spectroscopy for cattle urine have been reviewed. The presented information might open doors for the further characterization of cattle resources for heterogeneous applications in the production of utility items and addressing research gaps. Graphical Abstract: Methods for cattle’s dung and urine characterization [Figure not available: see fulltext.] © 2023, The Author(s), under exclusive licence to Springer Nature B.V.